PENGARUH MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. SEAFOOD NUSANTARA KABUPATEN TOLITOLI - Burhanuddin Burhanuddin; Samsidar Samsidar (Economy Deposit Journal (E-DJ), 2019)
The problem in this study is how much influence the motivation has on employee performance at PT. Seafood Nusantara Tolitoli Regency? The purpose of this study was to determine how much influence motivation on employee performance at PT. Seafood Nusantara Tolitoli Regency. This research was conducted at PT. Seafood Nusantara Tolitoli Regency. Data collection techniques by means of observation, interviews, and questionnaires. The population and sample in this study were employees of PT. Seafood Nusantara Tolitoli Regency, amounting to 35 people. The sampling technique in this study uses "Saturated Samples". Associative data types, data sources from primary data and secondary data, data analysis methods used are moment product correlation, coefficient of determination and likert scale. Correlation coefficient (r) = 0.61 or 61% is a positive number. This shows the relationship between motivation (X) and employee performance (Y). While the coefficient of determination (r)2 = 0.3721 or 37.21% which means motivation affects employee performance, while the remaining 62.79% is influenced by other factors not examined in the research conducted.